MANAJEMEN KELEMBAGAAN USAHA MIKRO MENENGAH (UMKM) PENGELOLAAN HASIL KERAJINAN ROTAN DI KELURHANA BUKIT TUNGGAL KECAMATAN JEKAN RAYA KOTA PALANGKARAYA - Muhamad Yusuf (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
Poverty reduction is a top priority in the implementation of national development. The government is obliged to increase the level of welfare, quality and survival of the community as well as increase the ability and awareness of the community in implementing social welfare in an institutionalized and sustainable manner. One of the efforts that has been developed to improve people's welfare is through the development of the real economy in communities based on micro and medium economics (MSMEs). The role of MSMEs is currently one of the spearheads in restoring people's economic conditions, especially after the pandemic where there was a drastic decline in people's economic activities. Through community service activities that focus on MSME development, it is hoped that the community's economy will gradually increase and as an effort to support the management of local resources and potential. The implementation of community service is carried out in the Bukit Tunggal Village, Jekan Raya District, Palangkaraya City, by looking at how the institutional management of MSME management, especially the business of managing rattan products is carried out by the community. Optimizing the role of MSMEs to create jobs and improve the community's economy in a sustainable manner, as well as increasing networks in collaboration with various parties.